1998
DOI: 10.1038/emm.1998.23
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum retention and degradation of T cell antigen receptor β chain

Abstract: The T cell antigen receptor-CD3 (TCR/CD3) complex is assembled in the endoplasmic reticulum (ER) of T cells after synthesis of individual chains, and is transported to the cell surface for immune recognition and regulation. Partially assembled or unassembled TCR chains are retained and rapidly degraded in the ER. These processes are strictly regulated in the ER at post-translational level for the maintenance of cellular homeostasis. In order to identify the region responsible for the ER retention and rapid deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…We demonstrate in mouse T cells that newly synthesized TCR beta chain proteins are formed as DRiPs and this extends the earlier reported formation of DRiPs and their degradation in other cell types [2,3,27]. In HeLa cells transfected with cDNA of TCR␤ chain, more than 80% of newly synthesized TCR beta chain was retained in ER and rapidly degraded in ER [40]. HeLa cells do not express CD3 molecules.…”
Section: Discussionsupporting
confidence: 63%
“…We demonstrate in mouse T cells that newly synthesized TCR beta chain proteins are formed as DRiPs and this extends the earlier reported formation of DRiPs and their degradation in other cell types [2,3,27]. In HeLa cells transfected with cDNA of TCR␤ chain, more than 80% of newly synthesized TCR beta chain was retained in ER and rapidly degraded in ER [40]. HeLa cells do not express CD3 molecules.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, serinedependent ubiquitination is likely a conserved mechanism for ERAD of unassembled TCR␣ among mammals. The ␤-subunit of the TCR (TCR␤) is also degraded when it cannot assemble with other TCR subunits (27,40). TCR␤ from different mammalian species has a cytosolic tail of 5-7 amino acid residues that contains 2-3 lysine residues (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many ER proteins are glycosylated on asparagine residues within Asn-X-Ser/Thr sequons (1,3). It has been reported that the T cell receptor ␤-chain (TCR␤) populates two isoforms that vary in their degree of glycosylation and which are readily distinguished by SDS-PAGE (28,36). Although the majority of TCR␤ is glycosylated at two sites co-translationally, a species can be detected that is only glycosylated on a single site 35 S]cysteine/methionine for 1 h and chased for 1 h to allow maturation of the chaperones before lysing either in the presence of ATP or apyrase.…”
Section: Grp170 Directly Binds To Unfolded Ig Substrates In Vivo-mentioning
confidence: 99%